2015
DOI: 10.1149/2.0671508jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cathodic and Anodic Treatments of Carbon on the Electrode Kinetics of VIV/VVOxidation-Reduction

Abstract: Cyclic voltammetry and electrochemical impedance spectroscopy were used to examine several types of carbon electrodes in V IV /V V in H 2 SO 4 . The materials investigated included glassy carbon, graphite, carbon paper, reticulated vitreous carbon and carbon fibers. In all cases the electrode kinetics of the V IV /V V oxidation-reduction reactions are enhanced by cathodic treatment of the electrode and inhibited by anodic treatment. Pronounced activation typically occurs at potentials more negative than +0.1 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 66 publications
6
81
0
Order By: Relevance
“…21 Previously, we reported that electrochemical oxidation treatments enhanced the V 2+ /V 3+ reaction kinetics, whereas electrochemical reduction treatments enhanced the VO 2+ /VO 2 + reaction kinetics. 22,23 This was demonstrated using a range of carbon materials including glassy carbon, carbon paper, carbon xerogel, and carbon fiber electrodes.It is apparent that kinetics are dependent on the nature of the electrode surface; thus, it is important to investigate factors affecting ki- * Electrochemical Society Student Member.* * Electrochemical Society Member. * * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…21 Previously, we reported that electrochemical oxidation treatments enhanced the V 2+ /V 3+ reaction kinetics, whereas electrochemical reduction treatments enhanced the VO 2+ /VO 2 + reaction kinetics. 22,23 This was demonstrated using a range of carbon materials including glassy carbon, carbon paper, carbon xerogel, and carbon fiber electrodes.It is apparent that kinetics are dependent on the nature of the electrode surface; thus, it is important to investigate factors affecting ki- * Electrochemical Society Student Member.* * Electrochemical Society Member. * * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…Before use, electrodes were preconditioned as discussed later. In addition, to minimize any effects of electrode history, electrodes were also subjected to a normalization treatment 22,23 between experiments, consisting of three cycles, each of 60 s at −2.0 V and 60 s at +1.5 V.Linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) experiments on CFMEs and electrochemical treatments of felt for surface analysis by X-ray photoelectron spectroscopy (XPS) were performed in a standard three-electrode cell with a potentiostat/galvanostat (Solartron SI 1287) and an impedance phase analyzer (Solartron SI 1260). The cell had a platinum counter electrode and saturated Hg/Hg 2 SO 4 reference (mercury/mercurous sulfate …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 From VRB research, information has been gathered on the whole cell as well as on the cathode using the V(IV)/V(V) redox couple which is of interest in this work. Currently whole cell EIS analysis fails to decouple contributions from the anode and cathode, while half-cell measurements are generally not gathered in-situ 19,20 However Sun et al have presented in their work an in-situ EIS study using a dynamic hydrogen reference electrode positioned using the "sandwich" method in the cell. 21 Their results demonstrated that the anode is the limiting electrode in VRBs, contributing most of the losses.…”
mentioning
confidence: 99%